2016
DOI: 10.1007/s11126-016-9459-6
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Subjective Appraisal of Recovery Among People with Lived Experience of Schizophrenia in Poland

Abstract: The objective of this study was to explore definitions of recovery among Polish service users with lived experience of schizophrenia and to hear their recommendations regarding elements that should be considered in the planning of a recovery oriented psychosocial intervention. Four semi-structured focus groups were conducted in the Institute of Psychiatry and Neurology in Warsaw, Poland. A total of 28 service users' narratives were examined using the inductive thematic analysis approach. Five main recovery the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 25 publications
2
24
0
1
Order By: Relevance
“…The workshop was developed based on results from the systematic literature review (Nowak et al 2016) indicating that there is a need to develop more recovery-oriented interventions and a focus group study (Nowak et al 2017) that guided the development of workshop modules. As psychological recovery was the most widely supported theme, the first three modules focused on personal definitions of recovery, strengthening positive sense of self, and value-based goal setting, whereas the content of further modules referred to more objective recovery domains, such as self-management of mental and physical health as well as enhancing relationships with others.…”
Section: Recovery-oriented Cognitive Behavioural Workhopmentioning
confidence: 99%
“…The workshop was developed based on results from the systematic literature review (Nowak et al 2016) indicating that there is a need to develop more recovery-oriented interventions and a focus group study (Nowak et al 2017) that guided the development of workshop modules. As psychological recovery was the most widely supported theme, the first three modules focused on personal definitions of recovery, strengthening positive sense of self, and value-based goal setting, whereas the content of further modules referred to more objective recovery domains, such as self-management of mental and physical health as well as enhancing relationships with others.…”
Section: Recovery-oriented Cognitive Behavioural Workhopmentioning
confidence: 99%
“…Previous studies6 42 43 recommend community interventions targeted at maintaining a positive identity,6 which is related to decreasing the negative effects associated with self-stigma, such as low self-esteem, a lack of hope, lower compliance to treatment and a decrease in the quality of life 42. Within the recommended interventions,6 42 43 the development of meaningful occupations provides new opportunities for constructing alternative identities to that of the illness 16 40 44. Identities that are linked to work contexts have shown to facilitate the acquirement of a new self-concept that is different to the disorder, integrating the same into their personal and social identity 45…”
Section: Discussionmentioning
confidence: 99%
“…Results of the systematic review by Nowak et al (2016) indicated a need to develop more recovery-oriented CBT interventions, which can foster personal recovery and address the disabilities of people diagnosed with schizophrenia. To make the workshop meaningful for Polish service users, themes derived from the focus group study carried out by Nowak et al (2017) guided the development of the workshop's content. Seven modules were formulated and manualized, applying a wide variety of traditional and ‘third wave’ CBT techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive behavioural therapy (CBT) is a treatment of choice for psychosis, but few recovery-focused, cognitive behavioural interventions are available for schizophrenia as shown in a study by Nowak et al (2017). An evaluation of whether a CBT intervention targeting personal recovery can also support people diagnosed with schizophrenia in overcoming disabilities experienced in daily life is required as this could provide a more comprehensive strategy for the recovery of people with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation